Ẓawāhir al-Tikrār fī Murthīyāt al-Shā‘ir Bashīr al-Ḥāj Ghāji li-Tijānī al-Miskīn - Zakir Al Haj Shareef; Saleh Muhammad Kabir (Al-Ma‘rifah, 2020)
Repetition (al-tikrār) represents one of the most artistic and stylistic phenomena in contemporary critical studies. It is achieved a creative and aesthetic value in the literary discourse since it reveals us about the underlying real contents behind this sort of discourse. This paper seeks to monitor ’Repetition’ types and their impact in the formation of poems of Bashīr al-Ḥāj Ghāji through the investment of principles and mechanisms of the artistic approach in the structure analysis of the repetition in his poems. They are many types such as repetition in letter, word and phrase as well as derivational repetition. It was due to that repetition those structures the obvious impact in the giving of some of his poems a rhythmic dimension and a musical tune which share in the overall rhythmic structure as well as achieved some of the its semantic purposes which the poet tried to express it and deliver it to the recipient.